Bank branches as places of knowledge creation: conceptual considerations and empirical findings at the micro-geographical scale - Flögel, Franziska; Zademach, Hans-Martin (ERDKUNDE, 2017)
Taking recent advances on the connection of social dynamics and physical place in the geographies of knowledge creation debate as a starting point, the paper scrutinises bank branches as locations where social dynamics and physical place coincide. It presents original data gained inter alia by means of participatory observation on the credit-decision processes of both a private big bank operating nationwide and a regional savings bank in Germany. Our results first highlight the general role of physical characteristics of bank branches – most notably the arrangement in the workplace and the resulting degrees of accessibility and confidentiality – in processes of knowledge exchange and creation. In addition, our insights reveal that both bank executives and bank customers are well aware of this connection between physical characteristics and social dynamics, and thus strategically design their branches and select certain sites for negotiations.